3(v+1)=-2v-32

Simple and best practice solution for 3(v+1)=-2v-32 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(v+1)=-2v-32 equation:


Simplifying
3(v + 1) = -2v + -32

Reorder the terms:
3(1 + v) = -2v + -32
(1 * 3 + v * 3) = -2v + -32
(3 + 3v) = -2v + -32

Reorder the terms:
3 + 3v = -32 + -2v

Solving
3 + 3v = -32 + -2v

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '2v' to each side of the equation.
3 + 3v + 2v = -32 + -2v + 2v

Combine like terms: 3v + 2v = 5v
3 + 5v = -32 + -2v + 2v

Combine like terms: -2v + 2v = 0
3 + 5v = -32 + 0
3 + 5v = -32

Add '-3' to each side of the equation.
3 + -3 + 5v = -32 + -3

Combine like terms: 3 + -3 = 0
0 + 5v = -32 + -3
5v = -32 + -3

Combine like terms: -32 + -3 = -35
5v = -35

Divide each side by '5'.
v = -7

Simplifying
v = -7

See similar equations:

| -3t(2t-5)+4t=5t-9 | | 2x(x+1)-(x+1)=0 | | -.02k+1=11 | | 12s=89 | | 6+49x=21x+42 | | 2x+(x+12)=180 | | .02k+1=11 | | 9(x-2)=3(x-2) | | 4.5x-39=2.2x+7 | | n+n+m=2 | | -3t(4t-4)+8t=3t-4 | | 7x+4=x+10 | | x=y/6(16-z) | | -27x^2+48x-5= | | 4(t-3)=2t+7 | | -2(3t-4)+3t=2t-3 | | -27x^3+48x-5= | | 10x^2+2.5x-45=0 | | 3x+11=6x-4 | | 5+6=5+x | | 6x^2-4x=-11 | | 8+y=6+2y | | -5(3t-2)+2t=4t-9 | | x^4-8x^3+98x^2-648x+1377=0 | | 36m^-4n^-6/4mn^-2p^-4 | | -x^2-100=0 | | 19=4-2m-m+7 | | (2x+4)+(3x-13)=180 | | 20a+25= | | 12-4y=2(y+9) | | 2.50x=500+0.35x | | 16a+28= |

Equations solver categories